Págico: evaluating wikipedia-based information retrieval in Portuguese - Mota, Cristina (2012)
How do people behave in their everyday information seeking tasks, which often involve Wikipedia? Are there systems which can help them, or do a similar job? In this paper we describe Págico, an evaluation contest with the main purpose of fostering research in these topics. We describe its motivation, the collection of documents created, the evaluation setup, the topics chosen and their choice, the par- ticipation, as well as the measures used for evaluation and the gathered resources. The task—between information retrieval and question answering—can be further described as answering questions related to Portuguese-speaking culture in the Portuguese Wikipedia, in a number of different themes and geographic and temporal angles. This initiative allowed us to create interesting datasets and perform some assessment of Wikipedia, while also improving a public-domain open-source system for further wikipedia-based evaluations. In the pa- per, we provide examples of questions, we report the results obtained by the participants, and provide some discussion on complex issues.